2017
DOI: 10.15201/hungeobull.66.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Supporting transition toward conservation agriculture: a framework to analyze the learning processes of farmers

Abstract: Conservation agriculture (CA) is based on 3 principles, namely reduced soil disturbance, permanent soil cover, and more complex and legume-rich rotations; and multiple studies have shown its positive impacts. Because CA relies on a variety of ecological processes, it is more deeply rooted in a specific ecological context than conventional agriculture. The complexity of these processes makes it difficult to elaborate general recipes to be applied by farmers, who therefore need to learn to make their own choices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…The interplays between farmers' exchanges among collectives and the transition process agricultural practices, various studies have shown that transitions towards more sustainable farming systems actually lead to transformations of the farmers themselves: their worldview, their values, their work organization, and so on (Lamine, 2011;Chantre et al, 2013;Barbier et al, 2015;Coquil et al, 2017;Cristofari et al, 2017;Dupré et al, 2017;Chizallet et al, 2018;Toffolini et al, 2019). Although such studies were conducted for various purposes and through different approaches, they all point out that the transition process towards sustainability is much more complex than just filling knowledge gaps or adopting new recommended practices (Coquil et al, 2018).…”
Section: From An Analysis Of the Review To The Conceptual Frameworkmentioning
confidence: 99%
“…The interplays between farmers' exchanges among collectives and the transition process agricultural practices, various studies have shown that transitions towards more sustainable farming systems actually lead to transformations of the farmers themselves: their worldview, their values, their work organization, and so on (Lamine, 2011;Chantre et al, 2013;Barbier et al, 2015;Coquil et al, 2017;Cristofari et al, 2017;Dupré et al, 2017;Chizallet et al, 2018;Toffolini et al, 2019). Although such studies were conducted for various purposes and through different approaches, they all point out that the transition process towards sustainability is much more complex than just filling knowledge gaps or adopting new recommended practices (Coquil et al, 2018).…”
Section: From An Analysis Of the Review To The Conceptual Frameworkmentioning
confidence: 99%
“…For these scholars, the term "anchoring" conceptualize emerging forms of connection; that is, anchoring is about the link between a novelty and the existing structures and institutions. Therefore, anchoring might happen between a niche and a regime or within a niche like, for example, transformation observed in niche actors (worldviews, values, organization) when going through transitions towards more sustainable agricultural systems (Chizallet et al, 2018;Coquil et al, 2017;Cristofari et al, 2017;Dupré et al, 2017;Lamine, 2011;Toffolini et al, 2019). Elzen et al (2012) propose three anchoring types: technological, network, and institutional.…”
Section: Mlp Elements Conceptualization and Operationalizationmentioning
confidence: 99%
“…These forms of organisation, the main goal of which is to share knowledge and learn situated practices, also have the effect of re-drawing the boundaries of agronomic "standard practices". This entails redefining what constitutes good cropping practices, what a field is in a good state is like, what acceptable production levels are, or even the criteria for judging efficiency, and so on (Cristofari et al 2017). This way of organising knowledge circulation contributes to "valuing" others' viewpoints while simultaneously enabling the construction of a shared representation of collective values.…”
Section: The Diversified-globalised Model: a Compromise Between Opinimentioning
confidence: 99%